2022
DOI: 10.1037/per0000486
|View full text |Cite
|
Sign up to set email alerts
|

High convergent validity among the five-factor model, PID-5-SF, and PiCD.

Abstract: In the last 10 years, 2 instruments (the Personality Inventory for Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition [PID-5] and the Personality Inventory for International Classification of Diseases, 11th Revision [PiCD]) have been developed to measure the dimensional approach to personality disorders (PDs). Several studies have analyzed the relationships between both instruments and the five-factor model, although the PiCD has received less attention than the PID-5, given its more recent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 56 publications
7
14
0
Order By: Relevance
“…Similarly toSchmitz et al (2001), symptomatology from SCL-90-R was mainly related to N, with almost identical r-scores. Furthermore, as it was shown previously(García et al, 2022), the current results show a high conver-gent validity between the five-factor model and a measure of personality disorders. The study's main limitation was that the gains in convenience are met at the expense of loss of information concerning NEO-PI-R facets.…”
supporting
confidence: 88%
“…Similarly toSchmitz et al (2001), symptomatology from SCL-90-R was mainly related to N, with almost identical r-scores. Furthermore, as it was shown previously(García et al, 2022), the current results show a high conver-gent validity between the five-factor model and a measure of personality disorders. The study's main limitation was that the gains in convenience are met at the expense of loss of information concerning NEO-PI-R facets.…”
supporting
confidence: 88%
“…Histrionic PD showed a mixed pattern of small to moderate associations with Dissociality, Disinhibition, and Negative Affectivity, which aligns with the fact that this PD type is essentially characterized by self-centeredness and longing for attention (i.e., Dissociality), excitement and attention seeking (i.e., Disinhibition), and excessive and labile emotionality (i.e., Negative Affectivity). Two studies also indicated negative associations with Detachment ( 14 , 28 ), which is consistent with the extreme extraversion and emotional expressivity (e.g., reversed Detachment) characterizing Histrionic PD.…”
Section: Associations Between Personality Disorder Types and Icd-11 T...supporting
confidence: 55%
“…We used PubMed, PsycINFO, Web of Science, and a broad snowballing method to identify a total of nine relevant studies investigating associations between traditional PD types and ICD-11 trait domain scores (14,17,(24)(25)(26)(27)(28)(29)(30). We chose to include exclusively articles published after 2017, with the rationale being that ICD-11 has gone through a number of iterations, in which diagnostic definitions have undergone significant changes (5,(31)(32)(33)(34).…”
Section: The Current Reviewmentioning
confidence: 99%
“…To date, a number of studies have already investigated associations between self-reported ICD-11 trait domains and traditional PD types (Bach et al, 2018; Bach, Kerber, et al, 2020; Fang et al, 2021; García et al, 2022; Kim et al, 2021; Lugo et al, 2019; Sellbom et al, 2020; Sellbom et al, in press; Simon et al, 2023; Sorrel et al, 2022), which overall showed expected and conceptually coherent associations. However, associations have not yet been investigated with respect to clinician ratings performed by practitioners, which is deemed important because self-report bias seems to increase by the severity of personality pathology (e.g., Nuzum et al, 2019).…”
Section: International Classification Of Diseases (11th Edition; Icd-...mentioning
confidence: 99%